Pengaruh Membaca Cerpen Terhadap Minat Baca Siswa Kelas 4 SDN Wergu Kulon - Oktaviana Dwi Rahmadhani; Luluk Zakiatus Sholikhah; Umi Virgianti; Sherly Arinda May Listy; Dicky Amirul Hasan; Anggieta Yesenia Nirwana (Jurnal Lensa Pendas, 2023)
The purpose of this study was to determine the extent to which reading short stories can influence the reading interest of fourth grade students at SD 1 Wergu Kulon. To find out whether the fourth grade students' interest in reading at SD 1 Wergu Kulon has increased after being involved in reading short stories. The research was started by giving an instrument in the form of a questionnaire sheet to 13 fourth grade students and then doing it to test students' initial understanding in reading. This is influenced by several factors, one of which is internal factors that come from themselves, such as interest and awareness. Questionnaires filled out by students, it was found that more girls like reading than boys. Keywords: Short Stories, Reading, Elementary School